Monthly variability of chlorophyll-α concentration in Persian Gulf using remote sensing techniques - Sharifinia, Moslem; Penchah, Mohammadreza Mohammadpour; Mahmoudifard, Abbas; Gheibi, Abolhasan; Zare, Rohallah (Universiti Kebangsaan Malaysia, 2015)
During the last two decades, large-scale high biomass algal blooms of the dinoflagellate Cochlodinium have occurred frequently. Prior to 1990, blooms had been primarily reported in Southeast Asia. Since then, time blooms have expanded across Asia, Europe and North American. A multi-spectral classification and quantification technique is developed for estimating chlorophyll-α concentrations. In this study, we explored the use of Sea-viewing Wide Field of-view Sensor (SeaWiFS) satellite data in studying the spatio-temporal changes in chlorophyll-α concentration in Persian Gulf. In addition, the present study focuses on the temperature, dissolved oxygen, salinity, pH and nutrient concentrations during the red tide phenomenon. The resultant chlorophyll-α concentration images derived from SeaWiFS satellite data give an indication of the monthly spatial variation in chlorophyll-α concentration from 2008 to 2009. Variability of chlorophyll-α plot from September 2008 to May 2009 in Persian Gulf showed that September 2008 had the lowest value (1.57±0.14 mg m-3) than other years except May 2009, then tended to increase up to January 2009 (Highest value: 7.47±1.67mg m-3), then a slow decrease up to May 2009. The result showed all water physicochemical parameters measurement in-situ (DO and pH) and ex-situ (NO3 and PO4), were varied among the different months. The highest and lowest values of these parameters were recorded in September 2008 and May 2009, respectively. After occurrence of the red tide, nutrient concentration (NO3 and PO4), dissolved oxygen and pH were reduce compared to before this phenomenon. Compare mean between various months’ showed significant differences for temperature records among the months of study (p≤0.05). Lowest and highest temperature recorded were in February 2009 and September 2008, respectively, but no significant differences were found in salinity (p≥0.05). This study showed that SeaWiFS satellite data provide useful information on the spatio-temporal variations in Persian Gulf, which is useful in establishing general trends that are more difficult to determine through routine ground measurements.